Visual self-presentation through unique costumes: a case study of the digital persona of a “crackers man” on Instagram - Tyas, Bonifacia Bulan Aruming (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
This study examines how a “Crackers Man”, an Instagram content creator and crackers maker, publicly known through his Instagram account @jeniinugraha, utilizes distinctive costumes for visual self-representation and shaping a digital persona, which transcends the conventional perception of his profession. This study aims to analyze the strategies and impacts of this unconventional approach. A qualitative case study method was employed, utilizing in-depth content analysis of @jeniinugraha’s Instagram profile, semi-structured interviews with the creator, and a survey of audience perceptions. The main findings of this study suggest that the consistent use of thematic costumes combined with humorous messaging strategies contributes to the visual uniqueness of the content and an approachable digital persona. This study underscores the effectiveness of innovative visual communication for personal branding by micro-entrepreneurs on social media, offering a model for leveraging creativity to build distinction in crowded digital markets.